Extra-hepatic portal venous obstruction: the Scottish experience. (24th May 2012) - Cordiner, D; Devadason, D; Bishop, J; Bisset, M; Goudie, D
Abstract : Introduction/background: Extra-hepatic portal vein obstruction (EHPVO) is a significant cause of portal hypertension and gastrointestinal (GI) haemorrhage in children. Population based data on this rare condition is limited. Opinion is divided on the most appropriate management strategy with regards to serial therapeutic endoscopy versus the relatively new Meso-Rex shunt surgery. Aims: (1) To identify all cases of EHPVO in Scotland and describe the early presentation and diagnostic work up. (2) To study the long term outcome of this condition in the era of the Meso-Rex shunt. Methods: Multicentre collaborative study with retrospective longitudinal collection of data based on case note review. Information collected included demographic data, mode of presentation and endoscopic and radiological findings. Results: Thirteen patients were identified (8 male, 5 female). One was lost but the remaining twelve were followed up for a mean of 9.5 years (range 1-18 years). This represented 114 years of cumulative follow up. 6/13 (46%) presented with significant GI bleeds under the age of 5. 10/13 (77%) had significant perinatal factors that may have contributed to the origin of portal venous thrombosis. 8/13 (62%) had at least one abnormality on the thrombophilia screen. There were 25 episodes of GI bleeding that required hospitalisation and 20% of these episodes required blood transfusion. 7/13 (54%) have either already had a Meso-Rex shunt or are currently being considered for this surgery. Interestingly, none of the patients who had extended treatment with propranolol have proceeded to a shunt procedure. Ultrasound scanning was successful in making the diagnosis in the majority but often needed to be repeated before this was confirmed. Conclusion: The diagnosis of EHPVO requires a high index of suspicion. Unexplained gastrointestinal bleeding, particularly in the very young child should alert the clinician to the possibility of EHPVO. Perinatal risk factors may contribute to the origin of this rare disease highlighting the importance of a high standard of care in the neonatal period. Early consideration of the Meso-Rex shunt eliminates the need for therapeutic endoscopy and may result in reducing the risk of GI bleeds. Further collaborative study investigating this rare condition will help refine current practice.